Nanowire network-based photodetectors with imaging performance for omnidirectional photodetecting through a wire-shaped structure. Issue 59 (1st October 2018) - Wang, Shalong; Zou, Yousheng; Shan, Qingsong; Xue, Jie; Dong, Yuhui; Gu, Yu; Song, Jizhong
Abstract : A highly flexible, omnidirectional photodetector based on ZnO nanowire network was designed for the first time. The as-obtained wire-shaped PD has excellent flexibility (>500 cycles), large light on/off ratio of 10 3 and 360° no blind angle detecting. Abstract : Wearable photodetectors (PDs) have attracted extensive attention from both scientific and industrial areas due to intrinsic detection abilities as well as promising applications in flexible, intelligent, and portable fields. However, most of the existing PDs have rigid planar or bulky structures which cannot fully meet the demands of these unique occasions. Here, we present a highly flexible, omnidirectional PD based on ZnO nanowire (NW) networks. ZnO NW network-based PDs exhibit the imageable level performance with an on/off ratio of about 10 4 . Importantly, a ZnO NW network can be assembled onto wire-shaped substrates to construct omnidirectional PDs. As a result, the wire-shaped PDs have excellent flexibility, a large light on/off ratio larger than 10 3, and 360° no blind angle detecting. Besides, they exhibit extraordinary stability against bending and irradiation. These results demonstrate a novel strategy for building wire-shaped optoelectronic devices through a NW network structure, which is highly promising for future smart and wearable applications.